Pengaruh Brand Trust, Kemudahan Fintech, dan Risiko Terhadap Keputusan Pembelian Menggunakan Paylater Payment: (Studi Kasus di Kelurahan Gading RT. 10 RW. 07 Kota Surabaya) - Dea Rachmadany; Nuryadi Nuryadi; Syamsul Arifin (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
Rachmadany Dea, 1961201032, Effects of Brand Trust, Fintech Convenience, and Risk on Purchase Decisions Using the Paylater Payment (Case Study in Gading Village Rt. 10 Rw. 07 Kota Surabaya). This study aims to determine the effect of brand trust, fintech convenience, and risk variables on purchasing decisions using paylater payment feature in a case study in Gading Village, Rt. 10, Rw. 07 City of Surabaya. The sample in this study is 62. The variables of this study are brand trust, convenience, and risk. The model in this study uses multiple linear analysis, namely the classical assumption test and hypothesis testing which consists of the T test and the coefficient of determination. The results of this study indicate that: 1) Brand trust partially influences purchasing decisions. 2) Ease partially has no effect on purchasing decisions. 3) Partial risk has no effect on purchasing decisions.